Single‐Molecule Conductance of 1, 4‐Azaborine Derivatives as Models of BN‐doped PAHs. (12th February 2021) - Palomino‐Ruiz, Lucía; Rodríguez‐González, Sandra; Fallaque, Joel G.; Márquez, Irene R.; Agraït, Nicolás; Díaz, Cristina; Leary, Edmund; Cuerva, Juan M.; Campaña, Araceli G.; Martín, Fernando; Millán, Alba; González, M. Teresa
Abstract: The single‐molecule conductance of a series of BN‐acene‐like derivatives has been measured by using scanning tunneling break‐junction techniques. A strategic design of the target molecules has allowed us to include azaborine units in positions that unambiguously ensure electron transport through both heteroatoms, which is relevant for the development of customized BN‐doped nanographenes. We show that the conductance of the anthracene azaborine derivative is comparable to that of the pristine all‐carbon anthracene compound. Notably, this heteroatom substitution has also allowed us to perform similar measurements on the corresponding pentacene‐like compound, which is found to have a similar conductance, thus evidencing that B–N doping could also be used to stabilize and characterize larger acenes for molecular electronics applications. Our conclusions are supported by state‐of‐the‐art transport calculations. Abstract : Single‐molecule conductance of 1, 4‐azaborine acene‐type compounds was studied using the scanning tunneling microscope break‐junction technique. This substitution ensures an unambiguous electron path through both heteroatoms. A moderate change in conductance is observed when compared to the parent all‐carbon structure. State‐of‐the‐art transport calculations support the experimental results.